A Retrospective Analysis of the Impact of Metastasectomy on Prognostic Survival According to Metastatic Organs in Patients With Metastatic Renal Cell Carcinoma - Kim, Sung Han; Park, Weon Seo; Park, Boram; Pak, Sahyun; Chung, Jinsoo (Frontiers in Oncology, 2019)
This study evaluated the effects of metastasectomy on overall survival (OS) and progression-free survival (PFS) in metastatic renal cell carcinoma (mRCC) according to metastatic organs. The medical records (2005–2017) of 273 patients with mRCC were analyzed retrospectively to evaluate OS and PFS according to metastatic organs and their metastasectomy states. The Cox proportional hazard model was used to determine the prognostic significance of metastasectomy. The Kaplan-Meier curve and log-rank test were used to compare groups with different modalities and metastatic organs at a statistical significance of p<0.05. The overall median age was 57 years; 175 (64.3%) and 83 (30.4%) patients received cytoreductive nephrectomy and metastasectomy, respectively. The metastasectomy group was significantly younger and had a lower clinical T stage with significantly better PFS/OS (20.2/32.0 vs. 9.7/12.8 months) than that in the non-metastasectomy group (N=190, p<0.05). Liver with lung metastases were the worst metastatic combination for survivals in which liver metastasis was the only significant unfavorable risk factor for both PFS (HR 1.67) and OS (HR 1.74) (p<0.05). Multivariable analysis confirmed that metastasectomy was a significant favorable risk factor for PFS (HR 0.70) and OS (HR 0.56) (p<0.05) along with non-clear cell type (HR 0.61 for PFS), whereas the nuclear grade and poor Heng risk group were unfavorable risk factors (HR>2.0) for both PFS and OS (p<0.05). Metastasectomy and the affected metastatic organs significantly influenced prognostic survival in mRCC.